Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Tokopedia Shunyang Marine Fish di PT. Indotama Putra Wanana, Bekasi - Sumarni Sumarni; Rahmayati HM; Muh. Ali Situju (Institut Nalanda, 2024)
This research aims to determine the influence of service quality on customer satisfaction at Tokopedia Shunyang Marine Fish at PT. Indotama Putra Wahana, Bekasi. The sample used was 30 Tokopedia Shunyang Marine Fish customers who made purchases. The sampling technique in this research used accidental sampling. Data collection was carried out using a questionnaire with a Likert scale. The analytical method used in this research is a simple regression analysis method with the SPSS 26 application. The research results based on (t test) show that service quality has a significant effect on customer satisfaction with a significance value of 0.000 < 0.05. The results of the Coefficient of Determination test obtained an R Square of 0.980. This shows that the dependent variable customer satisfaction is 98.0% influenced by the independent variable service quality, while 2.0% is influenced by other variables that have not been examined in this research.